2021
DOI: 10.1021/acs.joc.0c02827
|View full text |Cite
|
Sign up to set email alerts
|

Base-Catalyzed H/D Exchange Reaction of Difluoromethylarenes

Abstract: The budding deuteriodifluoromethyl group (CF2D) is a potentially significant functional group in medicinal chemistry. Herein, we investigated t-BuOK-catalyzed H/D exchange reaction of difluoromethylarenes in DMSO-d 6 solution. The method provides excellent deuterium incorporation at the difluoromethyl group. Meanwhile, the effect of a trace amount of D2O in DMSO-d 6 solution on the deuteration reaction was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 58 publications
1
25
0
Order By: Relevance
“…Furthermore, we found the relative deuterated yield for other pyridine derivatives, N , N ‐dimethylpyridin‐4‐amine, 4‐( tert ‐butyl)pyridine, 2‐(4‐(trifluoromethyl)phenyl)pyridine, 2,2′‐bipyridine, 4‐chloro‐7‐(trifluoromethyl)quinoline, quinoline and phenanthroline, can also be consistent with an anionic mechanism (Figure S11.1–S11.7). Besides, excellent correlation between relative thermal stability of anionic species and deuteration yield are also found for other experimental results [25,28b] of the remote deuteration of pyridine derivatives, such as pyridine, 3,4‐dimethylpyridine, 2,3‐dimethylpyridine, 2‐bromopyridine, 2‐bromo‐5‐methylpyridine, 6‐bromonicotinonitrile and 1‐(difluoromethyl)‐4‐fluorobenzene (Figure S11.8–S11.14), as well as the deuteration of bioactive molecules in our own scope (caffeine, Figure S11.15). Using the anion stabilities, we have been able to successfully predict the order of deuterium incorporation in the different positions of new substrates (Scheme 6, Figure S11.16–S11.19).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, we found the relative deuterated yield for other pyridine derivatives, N , N ‐dimethylpyridin‐4‐amine, 4‐( tert ‐butyl)pyridine, 2‐(4‐(trifluoromethyl)phenyl)pyridine, 2,2′‐bipyridine, 4‐chloro‐7‐(trifluoromethyl)quinoline, quinoline and phenanthroline, can also be consistent with an anionic mechanism (Figure S11.1–S11.7). Besides, excellent correlation between relative thermal stability of anionic species and deuteration yield are also found for other experimental results [25,28b] of the remote deuteration of pyridine derivatives, such as pyridine, 3,4‐dimethylpyridine, 2,3‐dimethylpyridine, 2‐bromopyridine, 2‐bromo‐5‐methylpyridine, 6‐bromonicotinonitrile and 1‐(difluoromethyl)‐4‐fluorobenzene (Figure S11.8–S11.14), as well as the deuteration of bioactive molecules in our own scope (caffeine, Figure S11.15). Using the anion stabilities, we have been able to successfully predict the order of deuterium incorporation in the different positions of new substrates (Scheme 6, Figure S11.16–S11.19).…”
Section: Resultssupporting
confidence: 83%
“…Further, some bioactive molecules could be successfully labeled applying our methodology (Scheme 3, compounds 29 – 37 ). For these molecules, deuterium was not only incorporated in heterocycles (Scheme 3, compounds 29‐ d , 30‐ d , 33‐ d 3 , 34‐ d 3 , 36‐ d 3 , 37‐ d ) but also in chloro‐substituted arenes (Scheme 3, 32‐ d , 34‐ d 11 , 35‐ d 4 ) as previously reported for HIE reactions using KO t Bu and DMSO‐ d 6 [28b] …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The maximum mobility of devices is ≈1.2 cm 2 V −1 s −1 . [ 127 ] In order to produce high‐quality thin film, researchers usually combine the thermal evaporation with other techniques. Zone‐casting was first used to form C8‐BTBT parallel ribbons and then supplementary C8‐BTBT was deposited by thermal evaporation in high‐vacuum environment ( Figure a).…”
Section: Fabrication Techniques Of Btbt Derivative Thin Filmmentioning
confidence: 99%
“…In these two devices, a representative organic semiconductor of C 8 ‐BTBT was selected as the conducting layer because of its superior carrier mobility and good film‐forming character. [ 50–53 ] As for CTB layer, here another organic semiconductor of TAPC was used with the consideration of its appropriate mobility contrast with that of C 8 ‐BTBT, the matched energy level, as well as its wide use as the hole transporting layer in emitting devices. [ 19,54,55 ] Chemical structures of all materials used in this research are together shown in Scheme S1 in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%